A Highly Potent Class of Halogenated Phenazine Antibacterial and Biofilm-Eradicating Agents Accessed Through a Modular Wohl-Aue Synthesis - Hongfen Yang (Nature Portfolio, 2017)
Abstract Unlike individual, free-floating planktonic bacteria, biofilms are surface-attached communities of slow- or non-replicating bacteria encased within a protective extracellular polymeric matrix enabling persistent bacterial populations to tolerate high concentrations of antimicrobials. Our current antibacterial arsenal is composed of growth-inhibiting agents that target rapidly-dividing planktonic bacteria but not metabolically dormant biofilm cells. We report the first modular synthesis of a library of 20 halogenated phenazines (HP), utilizing the Wohl-Aue reaction, that targets both planktonic and biofilm cells. New HPs, including 6-substituted analogues, demonstrate potent antibacterial activities against MRSA, MRSE and VRE (MIC = 0.003–0.78 µM). HPs bind metal(II) cations and demonstrate interesting activity profiles when co-treated in a panel of metal(II) cations in MIC assays. HP 1 inhibited RNA and protein biosynthesis while not inhibiting DNA biosynthesis using 3H-radiolabeled precursors in macromolecular synthesis inhibition assays against MRSA. New HPs reported here demonstrate potent eradication activities (MBEC = 0.59–9.38 µM) against MRSA, MRSE and VRE biofilms while showing minimal red blood cell lysis or cytotoxicity against HeLa cells. PEG-carbonate HPs 24 and 25 were found to have potent antibacterial activities with significantly improved water solubility. HP small molecules could have a dramatic impact on persistent, biofilm-associated bacterial infection treatments.